Five-Month Incubation of Viviparous Deep-Water Shark Embryos in Artificial Uterine Fluid - Tomita, Taketeru; Toda, Minoru; Murakumo, Kiyomi; Kaneko, Atsushi; Yano, Nagisa; Nakamura, Masaru; Sato, Keiichi (Frontiers in Marine Science, 2022)
In this study, we developed an extra-uterine life-support system (artificial uterus) for viviparous elasmobranchs. Using this system, we maintained two embryonic specimens of the slendertail lantern shark (Etmopterus molleri) for approximately 5 months, the longest published record of the captive maintenance of the embryos of this species. This system is characterized by the use of a urea-containing artificial incubation fluid, of which the salinity and osmotic pressure are approximately equivalent to those of shark blood plasma. We hypothesized that this fluid reduces the salinity gradient between embryonic blood plasma and the environmental fluid, which thereby contributes to countering the low osmoregulatory capacity of viviparous shark embryos. However, the incubated specimens subsequently died during the process of seawater adaptation following “artificial birth.” Accordingly, information pertaining to uterine chemical dynamics throughout the gestation period is necessary for the design of a more effective incubation system. This technique will be relevant and may find application in conservation breeding at public aquaria in the future.